A lesson on interrogations from detainees: predicting self-reported confessions and cooperation - Snook, Brent (Criminal justice and behavior, 2015)
The ability to predict confessions and cooperation from the elements of an interrogation was examined. Incarcerated men (N = 100) completed a 50-item questionnaire about their most recent police interrogation, and regression analyses were performed on self-reported decisions to confess and cooperate. Results showed that the likelihood of an interrogation resulting in a confession was greatest when evidence strength and score on a humanitarian interviewing scale were high, and when the detainee had few previous convictions or did not seek legal advice. We also found that the level of cooperation was greatest when the humanitarian interviewing score was high, and when previous convictions were low. The implications of the findings for interrogation practices are discussed.